The Boundaries of Russian Identity Analysis of the Concept of Russkiy Mir in Contemporary Russian Online Media - Michał Kozdra (Lingua Cultura, 2018)
This article set out to present selected outcomes of my research on the concept of “russkiy mir” in contemporary ethnocentric online Russian media. Perspectives for further analysis were also presented. The analytical methodology involved a semantic and cultural analysis of a dataset from a cognitive and anthropological viewpoint including elements of critical discourseanalysis. The concept of “russkiy mir” in the ethnocentric discourse investigated in this article was based on an idea of forming a supranational Russian civilization. This community would unite all Russians, the Russian diaspora and all those learning Russia, and declaring the attachment to Russian culture. Proponents of this discourse assume that “russkiy mir” will have a geopolitical dimension, imperial pretenses and will transgress state borders, and claiming for itself a transcontinental realm. A nationality dimension is also supposed to be an important aspect according to the discourse participants. The main ethnos is to be that of the Russian nation, around which other ethnoses will congregate. The Orthodox religion is supposed to be an important co-constituent of “russkiy mir”.